Liderazgo transformacional y desempeño organizacional en las cooperativas de ahorro y crédito del segmento 1 de la ciudad de Latacunga. - Cabrera Parco, Erika Nathalia (2023)
This research is aimed at establishing the existence of a significant causal relationship between two variables: "transformational leadership" as an independent variable and "organizational performance" as a dependent variable, within the context of the Savings and Credit Cooperatives of segment 1 in the city. from Latacunga. To achieve this objective, a research design with a quantitative, correlational and explanatory approach was used, a methodology that involved exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). In the first instance, data was collected using two instruments recovered from previous studies published in scientific media, using a Likert scale with scores from 1-5. Then, with the available data, the exploratory factor analysis (EFA) was applied, allowing to identify the relationship and structure of the underlying variables of "transformational leadership" and "organizational performance". Subsequently, a confirmatory factor analysis (CFA) was developed, both individually for each construct and as a whole, in order to evaluate and confirm the underlying structure of the variables observed based on the previously specified theoretical model, thus validating the model constructs. proposed, and at the same time, checking more rigorously if the hypothetical model fits the observed data well. Finally, in this particular case, with the applied methodology it was possible to demonstrate that there is a relationship between transformational leadership and organizational performance in the Savings and Credit Cooperatives of segment 1 in the city of Latacunga.